(untitled) (Journal of the College of Basic Education, 2025)
The current research problem revolves around the role of the informative advertising poster in disseminating and developing cultural and societal awareness, as well as combating negative social phenomena that pose a threat to society. It is imperative to address such issues, including harmful daily habits and undesirable values, attitudes, and customs that are opposed by families and society. The aim is to build coherent communities based on sound principles and values for the sake of continuity and success. Thus, the research problem is encapsulated in the following question: What is the role of the informative poster in confronting and addressing negative social phenomena?The research aims to identify the role of informative posters in addressing social phenomena. Consequently, a number of posters relevant to the research topic were presented and analyzed. To achieve the research objective, the researchers employed the descriptive method in their analysis. The research community comprised a set of contemporary posters related to the topic of negative social phenomena in society, which were published on the international network (the internet). The research focused on the role of informative posters in confronting negative social phenomena, with the temporal boundary being the year 2023. The spatial boundary included global posters related to specific social phenomena such as addiction and domestic violence.The researchers arrived at several conclusions, including that the informative poster can be perceived and understood through its simple and direct idea, carrying clear values, symbols, and meanings. The design of informative posters is an art that promotes positive values in society and works to counter negative phenomena and values among community members, striving to modify their behaviors